Globalizing capital a history of the international monetary system - Eichengreen, Barry J. (Princeton University Press, 2019)
"First published more than a decade ago, Globalizing Capital has remained an indispensable part of economic literature. This classic book emphasizes the importance of the international monetary system for understanding the international economy. The second edition, published in October 2008, has consistently appeared on syllabuses since its release. The new, third edition of Globalizing Capital will extend the book's account of the development of the international monetary and financial system to cover the most recent eventful decade. The new chapter, to be placed immediately before the conclusion, will be entitled 'Brave New World' and will commence with the eruption of the 2007 Subprime Crisis and 2008 Global Financial Crisis. Subsequent sections will then describe and analyze the Greek debt crisis, the euro crisis, the 'currency wars' problem starting in 2011, and China's efforts to internationalize its currency, the renminbi, and re-make the global monetary and financial system along less dollar-centric lines. It will close with discussion of the implications of the Trump presidency for the future of international financial relations"--